The Relationship between Body Mass Index and the Pervasiveness of Ischemic Heart Disease in Patients with Type 2 Diabetes - Shah Zeb, Nadia Shah, Muhammad Ikram Shah, Muhammad Iqbal Qasim, Parveen Akhtar, Amir Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The conversion from transmissible to non-communicable diseases has taken place for numerous years in all states of the biosphere, including emerging republics. Ischemic heart disease and diabetes mellitus complications belong to the diseases of the second most important group. In current ages, there has been a renewed debate about the importance of weight gain and obesity as risk factors for both diseases. The Aim of the Study: is to govern the association amid the body mass index and the occurrence of ischemic heart disease in patients with type 2 diabetes. Methods: This cross-sectional study was conducted in the medicine department of Jinnah medical college Peshawar for the duration of 06 months from November 2020 to April 2021. The study was directed among 300 patients with type II diabetes mellitus. Data was collected from medical records and then analyzed using the SPSS with Chi-square method. Results: Out of 300 patients with type-II diabetes mellitus, 120 were men and 180 were women. According to the findings of the present study, among patients with type-II diabetes mellitus, 41 (13.7%) had ischemic heart disease, of which 29 were female and 12 were male. The ischemic heart disease prevalence in youth is in 11(26.8%) middle-aged and elderly is 53.7% (22 out of 41 patients) and 19.4% (8 cases out of 41 patients) respectively. Conclusions: Conferring to our conclusions, although the incidence of type-II diabetes in obese and overweight patients is advanced than in those with normal or low body weight, the incidence of ischemic heart complications in subjects with type 2 diabetes does not follow this trend. Varying body mass index and the incidence of coronary heart disease are higher in women than in men in the normal weight group.